2022
DOI: 10.1101/2022.02.07.479467
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salp blooms increase carbon export 5-fold in the Southern Ocean

Abstract: The Southern Ocean (SO) contributes substantially to the global biological carbon pump (BCP). Salps in the SO, in particular Salpa thompsoni, are keystone grazers that produce large, fast-sinking fecal pellets with high export potential. In a first study of this kind, we conducted Lagrangian experiments to quantify the salp bloom impacts on export pathways by contrasting locations differing in salp bloom presence/absence. We show that blooms increased particle export by ~5-fold, and exported up to 46% of net p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Using mean values from Figure 6 , and NPP above, including all salp‐mediated export processes, increases the E z ratio to 18%, which is 1.5‐fold higher than the E z ratio calculated excluding salp‐mediated export of 12% (Table 1 ). Similarly, a recent study in the Southern Ocean found that the E z ratio of 5%–10% in waters without salps increased to 42%–46% in waters with salps, due to the export of salp fecal pellets (Décima et al., 2022 ).…”
Section: Discussionmentioning
confidence: 86%
“…Using mean values from Figure 6 , and NPP above, including all salp‐mediated export processes, increases the E z ratio to 18%, which is 1.5‐fold higher than the E z ratio calculated excluding salp‐mediated export of 12% (Table 1 ). Similarly, a recent study in the Southern Ocean found that the E z ratio of 5%–10% in waters without salps increased to 42%–46% in waters with salps, due to the export of salp fecal pellets (Décima et al., 2022 ).…”
Section: Discussionmentioning
confidence: 86%